Modified Blended Learning in Engineering Higher Education during the COVID-19 Lockdown-Building Automation Courses Case Study - Andrzej Ożadowicz (MDPI AG, 2020)
The blended learning method with its supporting electronic tools is a very well-known approach in academic education. In most of its practical applications, direct face to face contacts between students and the teacher as well as students with each other in groups are important elements in the organization of lectures and classes. This is of particular importance in conducting laboratory classes in teaching process for engineers. However, the COVID-19 lockdown in the spring of 2020 closed schools, universities and completely eliminated the possibility of direct interpersonal contacts. These extraordinary circumstances forced changes in the organization of the teaching process, in particular the introduction of distance learning. Therefore, this paper proposes a modified blended learning method as well as describes a case study on its introduction in the education of building automation engineers at a technical university. A new organizational structure of this modified method is presented, with discussion of tools and methods of active distance learning, introduced during the COVID-19 lockdown period. Finally, some experiences, general reflections along with the identification of the preferred forms of distance learning by students are presented. The future works are briefly described as well.